2012
DOI: 10.4067/s0718-95162012000200014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorus and organic fertilizers on phosphorus fractions in submerged soil

Abstract: This study was conducted in order to evaluate effects of phosphorous fertilizer (PF)s from sources of triple superphosphate (TSP) and di-ammonium phosphate (DAP) and organic fertilizer (OF)s from sources of cow dung manure (CDM) and municipal solid waste compost (MSWC) on phosphorous (P) fractions include aluminium-P (Al-P), iron-P (Fe-P), Reductant soluble-P (RS-P), calcium-P (Ca-P) and available-P (Olsen-P) fractions under rice cultivation condition. The trials were carried out in calcareous and acidic soils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 27 publications
5
19
1
Order By: Relevance
“…These results agree with those from Abolfazli et al (2012), in which P adsorption in acid soils occurred preferentially in the iron fractions.…”
Section: Resultssupporting
confidence: 92%
“…These results agree with those from Abolfazli et al (2012), in which P adsorption in acid soils occurred preferentially in the iron fractions.…”
Section: Resultssupporting
confidence: 92%
“…HCl-Pi distribution decreased from 89% in control to 69% and 42% in 2 and 4% vermicompost treatments (Figure 4). Calcium phosphates are thermodynamically the most stable P minerals, although they were found to decrease in greenhouse studies (Guo et al, 2000;Uygur and Karabatak, 2009).The result is similar to the study of Abolfazli et al (2012) who reported that Ca-P mineral reduced following application of cow dung manure. in amended and non-amended soil, calcium phosphate minerals comprised the largest fraction of soil Pi indicating that the added P was transformed into the stable Ca-P minerals at the end of the experiment.…”
Section: The Pi Extracted By Naoh Is Considered As Pi Associatedsupporting
confidence: 83%
“…It maintains biochemical, metabolic functions in plants; maintains soil fertility and soil health [3]. But lower phosphorus use efficiency limits crop yield and economic return [4].…”
Section: Introductionmentioning
confidence: 99%